2022
DOI: 10.1136/jnnp-2022-329633
|View full text |Cite
|
Sign up to set email alerts
|

Application of the 2021 EAN/PNS criteria for chronic inflammatory demyelinating polyneuropathy

Abstract: BackgroundThe diagnostic value of new criteria of the European Academy of Neurology/Peripheral Nerve Society (EAN/PNS) for chronic inflammatory demyelinating polyneuropathy (CIDP) is unknown.MethodsWe performed a retrospective study of fulfilment of EAN/PNS 2021 criteria on 120 consecutive patients with a clinical diagnosis of ‘suspected CIDP’ and objective treatment response, attending University Hospitals Birmingham, UK. Specificity was evaluated versus 100 consecutive controls.ResultsThe sensitivity of EAN/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…There have so far been two studies that investigated the sensitivity and specificity of the EAN/PNS 2021 criteria and compared them with the EFNS/PNS 2010 criteria. 14,15 Of these, a multicenter study using an Italian CIDP database, reported that the EAN/PNS 2021 criteria showed lower sensitivity and higher specificity than the EFNS/ PNS 2010 criteria, 14 findings consistent with our results. A singlecenter study from the UK, which used a strict alternate reference standard (objective response to treatment) for a CIDP cohort similar to our study, reported equivalent sensitivity and specificity of both criteria and that the addition of the SCS criteria to the updated version showed no added diagnostic value.…”
Section: Discussionsupporting
confidence: 90%
“…There have so far been two studies that investigated the sensitivity and specificity of the EAN/PNS 2021 criteria and compared them with the EFNS/PNS 2010 criteria. 14,15 Of these, a multicenter study using an Italian CIDP database, reported that the EAN/PNS 2021 criteria showed lower sensitivity and higher specificity than the EFNS/ PNS 2010 criteria, 14 findings consistent with our results. A singlecenter study from the UK, which used a strict alternate reference standard (objective response to treatment) for a CIDP cohort similar to our study, reported equivalent sensitivity and specificity of both criteria and that the addition of the SCS criteria to the updated version showed no added diagnostic value.…”
Section: Discussionsupporting
confidence: 90%
“…The best balance between sensitivity (88% for possible CIDP and 81% for CIDP) and specificity (86% for possible CIDP and 97% for CIDP) was achieved when at least four motor and four sensory nerves were tested on electrodiagnostic studies. 15,16 Generally speaking, a demyelinating pattern is present on electrodiagnostic testing with abnormalities noted in motor and sensory nerves.…”
Section: Clinical and Electrophysiologic Featuresmentioning
confidence: 99%
“…Two 2022 validation studies of the EAN and Peripheral Nerve Society 2021 diagnostic criteria showed that these criteria are roughly equivalent to the European Federation of Neurological Societies and Peripheral Nerve Society criteria and tend to improve the diagnostic accuracy of CIDP variants. The best balance between sensitivity (88% for possible CIDP and 81% for CIDP) and specificity (86% for possible CIDP and 97% for CIDP) was achieved when at least four motor and four sensory nerves were tested on electrodiagnostic studies 15,16 . Generally speaking, a demyelinating pattern is present on electrodiagnostic testing with abnormalities noted in motor and sensory nerves.…”
Section: Chronic Inflammatory Demyelinating Polyradiculoneuropathymentioning
confidence: 99%
“…Two JNNP studies reported the sensitivity and specificity of the 2021 EAN/PNS criteria, and the results are compared with those of the 2010 EFNS/PNS criteria 3 4. Doneddu et al described results of an Italian multicentre study based on Italian CIDP registry database (n=330),3 whereas Rajabally et al reported analyses on a CIDP cohort of a single centre in the UK (N=120) 4 Table 1. summarises the results of the two studies.…”
Section: The First Validation Studies Of the 2021 Ean/pns Criteria Fo...mentioning
confidence: 99%
“… 3 4 Doneddu et al described results of an Italian multicentre study based on Italian CIDP registry database (n=330), 3 whereas Rajabally et al reported analyses on a CIDP cohort of a single centre in the UK (N=120). 4 Table 1 summarises the results of the two studies. Both studies show very high specificity, 98% and 94%, respectively.…”
Section: The First Validation Studies Of the 2021 Ean/pns Criteria Fo...mentioning
confidence: 99%